Association Between Hyperlipidaemia and Selected Cholestatic Markers in 74 Dogs with Suspect Acute Pancreatitis - Adrien J. Da Silva; Aimee Hope; Carmel T. Mooney (Animals)
The association between hyperlipidaemia and acute pancreatitis is unknown in dogs. This study aimed to investigate the association between hyperlipidaemia and other markers of cholestasis in dogs with suspect acute pancreatitis. Case records of dogs with suspect acute pancreatitis were retrospectively reviewed. Dogs that had pre-existing disorders or drug therapies associated with hyperlipidaemia, hypocholesterolaemia, or incomplete biochemical data were excluded. In total, 74 dogs met the inclusion criteria. There were 33 (44.6%) dogs with hypercholesterolaemia (HC) and 41 (55.4%) without (NC). Increased triglyceride concentrations were significantly (p = 0.005) more common in HC dogs (n = 13, 39.4%) compared with NC dogs (n = 4, 9.8%), but no value exceeded 5 mmol/L. The ALP activity was significantly higher in the HC group compared to NC group (932 (461–7271) and 380 (135–1312) IU/L, respectively, p = 0.001). There was a moderate positive correlation between cholesterol concentration and ALP activity (r = 0.498, p < 0.001) and a weak positive correlation between cholesterol concentration and gamma-glutamyl transferase activity (r = 0.296, p = 0.011). Cholesterol concentration was correlated with ALP and GGT activities suggesting an association between cholestasis and hypercholesterolaemia in dogs with acute pancreatitis.